CONTEXTUAL TEACHING AND LEARNING IN LEARNING ENVIRONMENTAL POLLUTION: THE EFFECT ON STUDENT LEARNING OUTCOMES - Ria Claudia Welerubun; Hengky L. Wambrauw; Jeni Jeni; Daniel Wolo; Insar Damopolii (Program Studi PGSD Universitas Flores, 2022)
Contextual Teaching and Learning (CTL) is a learning concept helps teachers relate subject concepts to real-world situations and student engagement to find materials learned and connect in everyday life. This study aims to determine the influence of CTL to improve student learning outcomes on environmental pollution materials during pandemics. The research was conducted at Manokwari Advent Junior High School in April-May 2021. The sample of learning grade VII A (experimental class) number of learners as many as 22 people and grade VII B (control class) the number of learners 20 people. This research method was quasi-experimentation with a nonequivalent control group design, an instrument used in research in the form of cognitive tests in the form of multiple choice. Analysis of data mechanisms used in the study was a normality test, homogeneity testing, and followed by hypothesis testing using the SPSS IMB 20 mentoring program. After the test was obtained, the results of the learning class experimental have an average post-test of 86.25, while the value of the post-test control class is 45.25; then, it can be concluded that the CTL model can improve the learner learning outcomes